Empowering educators through STEM and local wisdom-infused learning with lesson study at SMAIT Al-Fityan Kubu Raya - Dedeh Kurniasih; Tuti Kurniati; Arya Girald Baihaqie; Elsi Oktaviyanti (Universitas Muhammadiyah Magelang, 2024)
Science, Technology, Engineering, and Mathematics (STEM) is an approach to learning in schools, including SMAIT Al-Fityan Kubu Raya. However, the school faces challenges in implementing STEM due to a lack of understanding and experience among teachers and the utilization of local wisdom. This community service program aims to assist SMAIT Al-Fityan Kubu Raya in designing STEM-based learning by integrating local wisdom through lesson study. The method used consists of four stages: 1) preparation, 2) socialization, 3) training and guidance for implementation, and 4) monitoring and evaluation. The results obtained from this program indicate that: 1) 92% consider STEM as something new, 2) 80% find the material easy to understand, 3) 75% believe there is suitability and interest among teachers in applying local wisdom-based STEM, and 4) 67% of teachers feel they are not yet able to implement STEM in their teaching. Participant understanding levels fall into the very good category with an N-Gain of 0.83. Therefore, the lesson study approach can enhance teachers' skills in designing and implementing chemistry learning by integrating STEM with local wisdom from West Kalimantan.